(untitled) (Communications in Computational Physics, 2020)
A new boundary condition, aimed at inhibiting near-wall condensation effects in lattice Boltzmann simulations of capillary flows in micro-corrugated channels, is introduced. The new boundary condition is validated against analytical solutions for smooth channels and demonstrated for the case of three-dimensional microflows over randomly corrugated walls.